Analisis Efektivitas Penerapan Aplikasi SIGNAL Dalam Peningkatan Pembayaran Pajak Kendaraan Motor Berbasis Digital di UPTD Samsat Padang - Fadhilla, Wireziyan; Melani, Vika Fania Ayu; Anfiska, Jihan; Arianti, Ririn; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research aims to determine the application of the SIGNAL application in increasing digital-based motor vehicle tax payments at the Padang City Samsat UPTD, as we know that the application of digital in the modern era makes it very easy to carry out certain matters, especially in paying taxes, the City Samsat has implemented the SIGNAL application which can make it easier for people to process tax payments, with this application, people don't need to make payments directly to the office. The lack of application of digital literacy among the community is the main challenge in implementing the SIGNAL application. However, the Padang City Samsat has provided education among the community with the help of the local government in the hope of overcoming the obstacles that exist in the community regarding the SIGNAL application.